An Efficient Synthesis of New Azide‐Nitrato‐Hydroxyl‐Terminated Polybutadiene by NaN3 and (NH4)2Ce(NO3)6. Issue 10 (9th August 2018) - Ghayeni, Hamid Reza; Razeghi, Reza; Olyaei, Abolfazl; Roosta, Saeed Tavangar
Abstract: This article reports way to functionalize hydroxyl‐terminated polybutadiene (HTPB) backbone by sodium azide and ceric ammonium nitrate, resulting in the formation of novel azide‐nitrato‐HTPB. In order to optimization of the effective parameters on the synthesis of azide‐nitrato‐HTPB, the starting material concentration, reaction time and temperature were investigated and the effect of these parameters on the azido‐nitrato functionalization of double bonds on HTPB backbone was evaluated. The functionalized HTPB by azidation (7.15 %) and nitration (5.17 %) showed viscosity of 17.6 Pa s −1, number average molecular weight of 2980 g mol −1 and hydroxyl value of 34 mg KOH per g. Abstract :